Surface studies on acrylic bone cement - Bettencourt, A (2015)
Poly(methyl methacrylate) (PMMA) is used to fill the gap between the prosthesis and the surrounding bone in cemented arthroplasties. Biocompatibility problems related to bone cement application limit the clinical success of these cemented arthroplasties. Being the cement surface in close connection with the living bone, it is reasonable to assume that surface properties such as, surface composition and surface energy, will play a role in the biomaterial performance. X-ray photoelectron spectroscopy (XPS) analysis and surface energy studies were carried out during 4 months, in order to assess a possible correlation between aging time and surface changes. The aging of PMMA, in a biological model fluid, strongly influences the composition and wettability of the cement surface. These changes may be explained through the hydrolysis of PMMA ester groups and the subsequent hydrogen bonding. Although our study does not exactly reproduce the in vivo environment surrounding a prosthesis, it suggests that the changes in the composition and wettability of the surface may modulate the host response towards the implant, thus contributing to its loosening. (C) 2004 Elsevier B.V. All rights reserved.